2019
DOI: 10.26434/chemrxiv.7312070.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of High Molecular Weight Chitosan from Chitin by Mechanochemistry and Aging

Abstract: Chitosan can be obtained from the deacetylation of chitin. This process is however difficult and usually accompanied by depolymerization, affording low molecular weight chitosan. We report a novel path, relying on a combination of mechanochemitry and aging, to afford high molecular weight chitosan with minimal use of energy and solvent. This method is versatile and applicable to a number of chitin sources, including crude crustaceans and insect shells, yielding deacetylation up to 98% and remarkably high molec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Very recently, it was demonstrated that mechanochemistry could be used to functionalize polymers with Schiff base moieties postproduction . Our group also reported a ball-milling method to effectively functionalize poly­(ethylene glycol) (PEG) with 5 different functional groups without affecting the main chain and a mechanochemical/aging one for the deacetylation of chitin to chitosan while maintaining high-molecular weight …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, it was demonstrated that mechanochemistry could be used to functionalize polymers with Schiff base moieties postproduction . Our group also reported a ball-milling method to effectively functionalize poly­(ethylene glycol) (PEG) with 5 different functional groups without affecting the main chain and a mechanochemical/aging one for the deacetylation of chitin to chitosan while maintaining high-molecular weight …”
Section: Introductionmentioning
confidence: 99%
“…16 Our group also reported a ball-milling method to effectively functionalize poly(ethylene glycol) (PEG) with 5 different functional groups without affecting the main chain 9 and a mechanochemical/aging one for the deacetylation of chitin to chitosan while maintaining high-molecular weight. 17 Phosphorylation is a key transformation to access biocompatible or flame-retardant materials, a class of chemicals able to slow the ignition and progression of fire. Regulations imposing the use of such molecules in construction, furniture, electronics, and textiles have had an overall positive effect on both the human and material costs associated with fires.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, chitosan can be produced by deacetylation of chitin, which is usually accompanied by a reduction in molecular weight due to some depolymerization. However, Di Nardo et al 43 reported that MS can produce chitosan with deacetylation levels ranging from 73% to 95%, while maintaining high molecular weights (see a summary of the MS protocol in Figure 4H). For this purpose, the amorphization of the initial polymer is a very important step, as crystallinity usually hinders the reactivity of polymers.…”
Section: Polymersmentioning
confidence: 99%
“…Amorphization is a common process whereby the crystallinity of a material is reduced by mechanical forces [17,24,5051] or otherwise [52] by deforming particles and breaking lattice imperfections [50]. For biomass processing, amorphization has been used in several studies [24,5354], either as a pretreatment [21] prior to deacetylation [18,55], enzymatic [22,5657] or acidic depolymerization [2324] and simultaneously during processing [42], yielding oligomers and monomers. Differentiating these regions of impact would be of great value for biomass processing.…”
Section: Introductionmentioning
confidence: 99%